Optimization of The General Cargo Loading Process to Increase Efficiency on The MV Hanglima Ship - Munir, Syahrul; Malik, Djamaludin; Anggraeny, Elva Febriana (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2024)
Research with the title "Optimizing the general cargo loading process to support efficiency on the MV Hanglima ship". Optimizing general cargo loading is very vital because more optimal loading will make MV Hanglima more able to compete with other ships or companies. This research aims to determine the factors that are obstacles that reduce efficiency in loading and to determine efforts to handle obstacles that occur when loading general cargo on the MV Hanglima. This research uses a qualitative descriptive method by using 5 data collection techniques including data from the prala location, namely the MV Hanglima ship. The theoretical basis used is a theory that includes 5 loading principles. And it was concluded that the loading of general cargo on the first trip on the MV Hanglima was less efficient, such as not paying enough attention to the stowage plan that had been made, which resulted in less systematic loading and broken stowage. Apart from that, the safety of ships, cargo, and workers and TKBM is still not paid enough attention so that it can be detrimental to the ship or shipping company, PBM, and workers.